Development of a Carrier Free Dry Powder Inhalation Formulation of Ketotifen for Pulmonary Drug Delivery - Azari, Fariba; Ghanbarzadeh, Saeed; Safdari, Rezvan; Yaqoubi, Shadi; Adibkia, Khosro; Hamishehkar, Hamed (Drug Research, 2020)
Background Pulmonary drug delivery route is gaining much attention because it enables to target the active ingredients directly to lung both for local and systemic treatments, which maximize the therapeutic effect and minimize unwanted systemic toxicity. Dry powder inhaler (DPI) systems for asthma therapy have shown several merits to the other pulmonary delivery systems such as nebulizers and metered dose inhalers.Purpose The present study aims to develop and optimize a DPI formulation for Ketotifen fumarate through spray drying technique.Methods Particles size and morphology, crystallinity, and drug-excipient interaction of fabricated DPI formulations were evaluated by scanning electron microscopy, X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier Transform Infrared Spectroscopy methods, respectively. The aerosolization indexes and aerodynamic properties of dry powders were determined by next generation impactor. The powder flowability was assessed by measuring the Hausner ratio and compressibility index.Results Among solvent systems, ethanol-water mixture produced the most desirable powder property for inhalation after spray drying. Although co-spray dried formulations with ammonium bicarbonate resulted in the porous structure, it was not beneficial for DPI formulations due to the interaction with Ketotifen. DSC and XRD experiments proved the amorphous structure of prepared powders, which were stable for 12 months.Conclusion The results of this study demonstrate the potential of Ketotifen DPI formulation and pave a way to use it easily in an industrial scale.
Keywords: Dry powder inhaler; DPI; Ketotifen; Pulmonary drug delivery; next generation impactor